MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR EKONOMI MELALUI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) SISWA KELAS X1 SMA NEGERI 1 ANGSANA KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN. - Selfi Gonaldy (JURNAL SOCIUS, 2015)
Improving Learning Activities and Learning Outcomes Through Cooperative Learning Economics Student Team Achievement Divisions (STAD) Student Class X1 SMA Negeri 1 Tanah Bumbu Angsana South Kalimantan Province. The purpose of this research is to increase the activity of learners class X1 in SMA Negeri 1 Angsana in the learning process is still low, the average value of daily tests on the material demand, supply, prices and the balance of 60, of 34 learners reach KKM as many as 15 learners and there are 19 students who have not reached the KKM.Keywords: Student Team Achievement Divisions (STAD), activities learning, learning outcomes